Régimen alimenticio de tres especies de peces ornamentales de la cuenca del río Nanay Loreto – Perú - Ismiño Orbe, Rosa Angélica (2024)
This work was carried out in the lower basin of the Nanay River (Loreto) during the months of September 2021 to August 2023, aiming to evaluate the feeding regime of three species of ornamental fish (Pterophyllum scalare, Biotodoma cupido and Petitella georgiae) and their relationship in hydrological periods of flooding and ebb, and to determine the composition of the stomach contents and preferential diets of said fish, the specimens were captured with a one inch fry net, they were collected in plastic buckets with 10% formalin, then they were washed and changed to buckets with 70% alcohol, in the laboratory they were weighed on a digital scale and measured with the help of an ichthyometer until they were eviscerated by the urogenital part, to extract the stomachs, they were weighed on an analytical balance, then the stomach contents were emptied into eppendorf tubes with 10% alcohol, they were observed in the stereoscope and microscope, were identified by means of dichotomous keys and what was found was recorded; having as results that P. scalare consumed phytoplankton (Charophytas, Euastrum sp., Bacillariophytas, Chlorophytas) detritus and zooplankton in their diet, consuming Cyclops sp. in juvenile stage, in crescent their diet increases; For B. cupido they ingest more zooplankton - Nais sp., Chironomus sp. And detritus in addition to phytoplankton, plant remains (leaf remains) are added; P. georgiae ingest more zooplankton (Aelosoma sp, Balatro sp) and detritus, the other items are low or almost null having as conclusions that the three species studied are omnivorous according to the diet.